Kain Tenun Cagcag pada Upacara Manusa Yadnya di Kelurahan Sangkaragung Kabupaten Jembrana - Ida Bagus Putu Eka Suadnyana (Jnanasidanta, 2020)
The manusa yadnya ceremony, the woven cloth is very synonymous in the community of Sangkaragung Village. Each region or regency in Bali is unique in its various motives and rules for its use. Traditionally woven fabrics are clothing used in the form of cloth that covers the body by both men and women, containing many elements such as history, fine arts and educational values. Why the cagcag woven cloth is used in the Manusa Yadnya ceremony is certainly very interesting to examine. In this study, the design and method used are qualitative research methods with data collection techniques, namely observation, interviews and document study. From the research results, it is found that the community uses the cagcag woven cloth in the manusa yadnya ceremony and the creation of the cagcag woven cloth still uses simple tools, but does not leave the traditions of their ancestors. From these findings, it can be concluded that, as a result of art, the community uses cagcag woven cloth at the manusa yadnya ceremony. 2, the process of making woven fabrics, the community still adheres to the customs and traditions in preserving the weaving craft in their village.